2013
DOI: 10.1155/2013/917082
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Carnosic Acid against Beta‐Amyloid Toxicity in Rats

Abstract: Oxidative stress is one of the pathological mechanisms responsible for the beta- amyloid cascade associated with Alzheimer's disease (AD). Previous studies have demonstrated the role of carnosic acid (CA), an effective antioxidant, in combating oxidative stress. A progressive cognitive decline is one of the hallmarks of AD. Thus, we attempted to determine whether the administration of CA protects against memory deficit caused by beta-amyloid toxicity in rats. Beta-amyloid (1–40) was injected by stereotaxic sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…Consistent with these findings, a previous study [52] in an experimental model of Alzheimer's disease in rats indicated that pretreatment with CA as an effective component of RE, can reduce neuronal death in hippocampus CA1. We also found that CA might ameliorate memory deficit beta-amyloid-induced toxicity in the rat hippocampus [53]. Considering that oxidative stress is one of the pathological mechanisms responsible for the beta-amyloid cascade associated with Alzheimer's disease, it appears that CA (as well as RE) plays multiple roles in the free radical chain reaction as an antioxidant.…”
Section: Discussionmentioning
confidence: 69%
“…Consistent with these findings, a previous study [52] in an experimental model of Alzheimer's disease in rats indicated that pretreatment with CA as an effective component of RE, can reduce neuronal death in hippocampus CA1. We also found that CA might ameliorate memory deficit beta-amyloid-induced toxicity in the rat hippocampus [53]. Considering that oxidative stress is one of the pathological mechanisms responsible for the beta-amyloid cascade associated with Alzheimer's disease, it appears that CA (as well as RE) plays multiple roles in the free radical chain reaction as an antioxidant.…”
Section: Discussionmentioning
confidence: 69%
“…Carnosic acid has been reported to protect the cells from various types of oxidative stress . Activation of the antioxidant defense system, Nrf2 activation, and subsequent production of phase II enzymes is a commonly accepted mechanism for the activity of CA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, carnosic acid was able to improve cognitive deficits in an Aβ40-induced AD rat model (Rasoolijazi et al, 2013). In another study, oral administration of ferulic acid, found in seeds and cereals, particularly flaxseed (Beejmohun et al, 2007), inhibited microglial activation in an Aβ42-induced AD mouse model by decreasing IFN-gamma levels in the hippocampus (Kim et al, 2004).…”
Section: Nutritional Approaches Towards Immunomodulation and Their Pomentioning
confidence: 99%